Functional set of axiological dominants within English discourse-communicative space - Yu. S. Starostina; I. V. Chekulai; O. N. Prokhorova (Вестник Самарского университета: История, педагогика, филология, 2021)
The article is devoted to the problem of multifunctionality of value dominants in the discourse space of English communication. The relevance of the study is determined by the fact that it is aimed at clarifying the conceptual guidelines of discourse-communicative linguoaxiology as a direction that is experiencing a stage of development of its own theoretical platform. English communication acts as a zone of manifestation of axiological attitudes, which serve as nuclear elements of both personal axiospheres of speakers and the social value system of English-speaking linguocultural communities. Nevertheless, the analysis of the functional system of axiological vectors has so far been sporadic and fragmentary. The article makes an attempt at the analysis of multifunctional loading of axiological dominants within the boundaries of the discourse field of English-based interpersonal communication. The purpose of the study is to develop a functional axiological set, i.e. a complex of interrelated functions fulfilled by value dominants in English discourse-communicative practices. The relevant methods of comparative content analysis and comparative analytical systematization have been employed as the methodological apparatus of the research. The results of the study consist in the formation of a five-component system-functional axiological set, implemented in the process of English communication, the analysis of functional potential of value dominants in terms of axiological levels, as well as the identification of the specificity of each component within the developed paradigm. Based on the results of the study, the authors formulate a reasoned conclusion that value dominants lay deep foundation that systematically defines the entire area of interpersonal communication due to the simultaneous realization of multifunctional potential. The components of functional axiological set, namely the social-regulatory, motivational, cultural-integrative, structure-forming and pragma-axiological functions, in the process of communicative actualization determine the speech behavior of those who participate in verbal interaction.